Implementation of Drone Technology in Logistic and Distribution Industry within the Scope of Jakarta Area - Inggrid Suparman, RapsodiAnugrah Telaumbanua, Gunawan Wang, Emil Robert Kaburuan (International Journal of Control and Automation, 2020)
This paper explains the model and benefit of Parcelcopter in Jakarta area. The reason of the implementation area the high traffic and pollution rate in Jakarta and to push Indonesia to move to Industry 4.0. Relating on how Industry 4.0 could really help Indonesia in some of their problem. Throughout the paper explanation cover the proposed business model for Parcelcopter and used case on how it will be performed in B2B and B2C. In conclusion Parcelcopter will be a new tool that are beneficial from business and society perspective, but since it is a new topic for Indonesians, government consent is necessary.